MAIN STAGES OF DEVELOPMENT OF THE DEPARTMENT OF POSTGRADUATE EDUCATION OF DOCTORSSTOMATOLOGISTS VGUZU UMSA - Skrypnykov P. M. (Вісник проблем біології і медицини, 2018)
The article describes the main stages of development and formation of the department of postgraduate education of doctors-dentists of the VSIA UMSA , an analysis of the work from 1991. The creation of the department was conditioned by the need for deepening of theoretical knowledge, improvement of the level of manual skills, preparation for independent professional medical activities of interns, completion of the postgraduate cycle of training of dental doctors. The article contains information about the heads of the department, types of activities and the structure of the educational process. The work of the department is described as a reference in the system of postgraduate education in specialties Dentistry , Therapeutic dentistry . Over this period, more than 46 typical curricula and programs have been created that have been introduced into the educational process of one-profile departments of higher educational institutions of Ukraine. In the center of constant attention of the department staff - improving the quality of the learning process, optimizing knowledge control methods, modern approaches to teaching. The article provides information on contemporary forms of learning, such as Brain-ring in dentistry , professional contests, the introduction of innovative technologies, the use of elements of distance education, which enhance the quality of the educational process. Since the year 2000, the All-Ukrainian Professional Competition for Doctors-Dentists The Way to the World of Excellence among the interns of the single-profile departments of higher educational institutions is being held for the introduction of new active forms of training that provide timely access to information for doctors, the Academic Training Center has been operating at the department. The regional stage of the International CERAM X CASE CONTEST (GCCC) International Restoration Clinical Competition Contest has been traditionally held.The introduction of innovations, innovative methods of diagnosis and treatment is carried out on the basis of collaboration of the department with private dental clinics and offices in the city of Poltava, manufacturers of dental materials. Today, the elements of distance education are actively being introduced into the work of the department. This allows you to read lectures, conduct practical classes, seminars during the pre-certification cycles without leaving the department of the department. Since 2008, the site of the department of postgraduate education of dentists is www.dentaero.com.